More than illustrated music: aesthetics of hybrid media between pop, art and video - Vomberg, Elfi; Dreckmann, Kathrin (New approaches to sound, music, and media, 2023)
The genre of the video clip has been established for more than thirty years, mainly served by the sub genres of video art and music video. This book explores processes of hybridization between music video, film, and video art by presenting current theoretical discourses and engaging them through interviews with well-known artists and directors, bringing to the surface the crucial questions of art practice. The collection discusses topics including postcolonialism, posthumanism, gender, race and class and addresses questions regarding the hybrid media structure of video, the diffusion between content and form, art and commerce as well as pop culture and counterculture. Through the diversity of the areas and interviews included, the book builds on and moves beyond earlier aesthetics-driven perspectives on music video